Implementasi P5 (Projek Penguatan Profil Pelajar Pancasila) Terhadap Pembentukan Karakter Siswa SMA Negeri 14 Kota Bekasi - Hatami, Muhammad; Afrizal, Stevany (CV. PUSDIKRA MITRA JAYA, 2025)
Education is a key driver of child growth, influencing the development of attitudes, values, and skills. The Merdeka Curriculum, launched in 2021 by the Ministry of Education and Culture, focuses on student learning freedom and integrates various features to maximize learning. The Pancasila Student Profile Reinforcement Project (P5) is a learning strategy designed to enhance students' Pancasila character and identity through authentic and relevant activities. This research used a qualitative method with a case study approach to evaluate the implementation of P5 at SMA Negeri 14 Kota Bekasi. The findings indicate that P5 not only strengthens student character but also promotes student literacy, including data, digital, and humanist literacy. P5 implementation involves planning, assessment management, report writing, and evaluation and follow-up stages, with a focus on developing student character in accordance with the Pancasila profile.